Embedded Engineering Education - Szewczyk, Roman; Kaštelan, Ivan.; Temerinac, Miodrag; Barak, Moshe; Sruk, Vlado; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book focuses on the outcome of the European research project "FP7-ICT-2011-8 / 317882: Embedded Engineering Learning Platform" E2LP. Additionally, some experiences and researches outside this project have been included. This book provides information about the achieved results of the E2LP project as well as some broader views about the embedded engineering education. It captures project results and applications, methodologies, and evaluations. It leads to the history of computer architectures, brings a touch of the future in education tools and provides a valuable resource for anyone interested in embedded engineering education concepts, experiences and material. The book contents 12 original contributions and will open a broader discussion about the necessary knowledge and appropriate learning methods for the new profile of embedded engineers. As a result, the proposed Embedded Computer Engineering Learning Platform will help to educate a sufficient number of future engineers in Europe, capable of designing complex systems and maintaining a leadership in the area of embedded systems, thereby ensuring that our strongholds in automotive, avionics, industrial automation, mobile communications, telecoms and medical systems are able to develop. .
Challenges in Embedded Engineering Education -- Unified Learning Platform for Embedded Engineering -- Exercises for Embedded Engineering -- Implementation of Advanced Historical Computer Architectures -- Methods for User Involvement in the Design of Augmented Reality Systems for Engineering Education -- Augmented Reality Interface for E2LP: Assistance in Electronic Laboratories though Augmented Reality -- E2LP Remote Laboratory: e-Learning Service for Embedded Systems Education -- Advanced Projects and Applications for Embedded Engineering on E2LP Platform -- E2LP Remote Laboratory: Introduction Course and Evaluation at Warsaw University of Technology -- Exploring Aspects of Self-Regulated Learning Among Engineering Students Learning Digital System Design in the FPGA Environment - Methodology and Findings -- Is It Possible to Increase Motivation for Study Among Sophomore Electricaland Computer Engineering Students? -- Interrupts Become Features: Using On-Sensor Intelligence for Recognition Tasks.
Keywords: Computational intelligence; Educational technology; Computational Intelligence; Digital Education and Educational Technology